1985
DOI: 10.1021/i200029a020
|View full text |Cite
|
Sign up to set email alerts
|

A novel coupling-dephenolization scheme for full-strength coal-conversion wastewaters: results of wastewater study and a cost analysis

Abstract: Results of a feasibility study using an actual coal-gasification wastewater confirm the promising nature of a coupling-dephenolization scheme which we have proposed previously. Kinetic results indicate that the aerobic coupling of phenols, which is the heart of the proposed scheme, occurs at a sufficiently high rate in the actual wastewater to make the scheme practical. A cost anal sis of the scheme indicates that for a commercial-scale coal gasification plant with a daily output of 200 X 10' J of synthetic na… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

1986
1986
1998
1998

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 5 publications
(9 reference statements)
0
6
0
Order By: Relevance
“…Reactions that may be advantageously conducted in an O-W interfacial mode include reactions that are potentially useful for materials synthesis and waste treatment, such as oxidative coupling reactions (Hay, 1962;Bach, 1968; Giles et al, 1986;Chin et al, 1985) and photocatalytic degradation reactions (Hackman, 1978;Sittig, 1985). The latter are of particular interest in light of the fact that the two commonly used photocatalysts, titanium dioxide and cadmium sulfide (MacKay, 1981;Henglein, 1984), are surface-active; see Table I.…”
Section: Resultsmentioning
confidence: 99%
“…Reactions that may be advantageously conducted in an O-W interfacial mode include reactions that are potentially useful for materials synthesis and waste treatment, such as oxidative coupling reactions (Hay, 1962;Bach, 1968; Giles et al, 1986;Chin et al, 1985) and photocatalytic degradation reactions (Hackman, 1978;Sittig, 1985). The latter are of particular interest in light of the fact that the two commonly used photocatalysts, titanium dioxide and cadmium sulfide (MacKay, 1981;Henglein, 1984), are surface-active; see Table I.…”
Section: Resultsmentioning
confidence: 99%
“…Consistently, Chin et al (1985) found that the rate of The degree of ionization of a sorbate does not seem to be the primary variable determing its reactivity on carbon, however. If it were, the lower the pKa value of a sorbate, the more reactive it should be in neutral aqueous solutions.…”
Section: Liquid Phase Propertiesmentioning
confidence: 90%
“…Basic aqueous solutions promote oxidation of phenolics (Penketh et al, 1957;Chin et al, 1985;and Previous studies have attempted to rationalize the differing abilities of solvents to regenerate phenol from activated carbon (Pahl et al, 1973;Knickmeyer et al, 1973;and Fuchs and Kuhn, 1976). In the first two studies, the solvents were held at 40oc, so surface reactions might have affected the results.…”
Section: Influence Of Temperature On Adsorption Amountsmentioning
confidence: 99%
“…The cost of this systemis $l.Wm3 of treated wastewater. This is much cheaper than alternate dephenolization schemes such as aerobic coupling (Chin et al, 1985), solvent extraction (Greminger et al, 19821, and bio-oxidation (Goldstein and Yung, 1977) whose costs are 4.31, 6.42 and 6.47 $/m3 of treated wastewater, respectively. These results suggest that the devised membrane-hybrid system can indeed be technically and economically effective in tackling dephenolization problems in coal liquefaction.…”
Section: Depeienolization Of Aqueous Wastesmentioning
confidence: 99%